Penerapan Metode Kompresi Wavelet dalam Pengolahan Data Gambar untuk Mengurangi Ukuran File - Paramita, Ni Putu Suci; Wibawa, I Gede Arta (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023DO - 10.24843/JNATIA.2023.v01.i04.p29, 2023)
Currently more and more computer users theincrease in the number of computer users has led to an increase digital data user. One of the most useddigital data today is digital images. The smallest element of a digital image is called pixels. The higher the number of pixels, the higher the  digital  resolution  picture.  The  higher  the  pixel  count,  the  larger  the  digital  image  file  size. Resulting  in fast full data storage capacity.Image data compression is an important  process in data processing and storage, especially with the increasing use of images in various applications and platforms. This study aims to apply the Wevalet compression method in processing image data to reduce file size. The Wevalet compression method combines the wavelet transform with an  adaptive  and  efficient  compression  breaking  procedure, toform  significant  compression without significant sacrifice of image quality.